Studi Praktek Agroforestri di Desa Talawaan Kecamatan Talawaan Kabupaten Minahasa Utara - Wendison Kogoya; R Kainde; W Nurmawan; A.G. Tulungen (COCOS, 2017)
ABSTRACTThe agroforestry system is a land use system, which has social and ecological aspects, implemented through a combination of trees with agricultural crops and / or livestock (animal) and / or fishery, either simultaneously or in rotation, so that from one unit of land is achieved the total yield of vegetable and / or optimal animals. (Nair, 1987). The practice of the agroforestry system has been done by the Talawaan villagers in the agricultural land management system, which combines forestry crops and agricultural crops. This research aims to know agroforestry land management practices in Talawaan Village Talawaan Subdistrict of North Minahasa Regency.This research was conducted in Talawaan Village Talawaan Subdistrict of North Minahasa Regency from July to August 2014. This research was conducted by interviewing the respondents about agroforestry practices. Based on the result of the research, there are 3 agroforestry system combinations of agrosilvopastur which are 15 garden samples (75%), silvopastur is 4 garden (20%), and agrosilvofisheri 1 garden sample (5%), with 7 type species. There are 14 combinations of commodities cultivated in agroforestry fields. There are 15 sample gardens with 9 combinations of timber tree species, 7 garden samples of woody horticultural plants or fruit trees with 12 combinations and 13 sample gardens with 9 plantation crop combinations.Keywords : Agroforestry practices, Combination of species groups